Technika mistyczna Abrahama Abulafii przedstawiona w ’Ocar ‘eden ha-ganuz = ABRAHAM ABULAFIA’S MYSTICAL TECHNIQUE PRESENTED IN ’OCAR ‘EDEN HA-GANUZ - Krawczyk, Mikołaj (Studia religiologica, 2008)
The text presents the prophetic kabbalistic mystical techniques described in ’Ocar ‘Eden ha-Ganuz [The Hidden Treasure of Eden] by the 13th-century Sephardic kabbalist Abraham Abulafia (1240- 1292?). Composed in Messina in 1285 for a disciple named Saadia, the book is considered as a mature explanation of the mystical system. Together with his ’Or ha-Sekhel [Light of the Mind] and Chayye ha-‘Olam ha-Ba [Life of the World to Come], it constitutes one of the essential texts of Abulafi an kabbalah and prophetic kabbalah as such. The article includes, for the first time in Polish translation, a large fragment of Abraham Abulafia’s book concerning an explication of mystical practice of one of the ways of chochmat ha-ceruf (“wisdom of combination”) and descriptions of Abulafia’s mystical experiences.